Development of wireless sensor network system - Varun, Eranian (2016)
In this world, there has been an increasing number of sensors deployed in our environment for various scientific studies. It may be to monitor the environment remotely or to monitor people’s behavior in the public. Many times, real time data from an array of sensor network is required. In this project, National Instrument’s myRIO is used for processing of acoustic data, gathered from the surroundings, and useful processed data is transmitted by using Xbee, which provide the wireless sensor network for the transmission. In this thesis, we will study about how useful processed environmental acoustic data from a mesh of multiple acoustic sensors can be transmitted to a central station. We will be able to study and analyze the noise level of the environment in real time and at the same time, monitor the health of each sensor. The traditional method of environmental sound sensing uses short term measurement periods using expensive equipment’s, set up and operated by experienced professional. The proposed project takes a different approach by implementing smart, lowcost, static, wireless, acoustic sensing device based around embedded systems. These devices can be deployed in numerous and varied urban locations for pro-longed periods of time from days to months, allowing for the collection and transmission of processed urban acoustic data.